2019
DOI: 10.1167/iovs.18-25986
|View full text |Cite
|
Sign up to set email alerts
|

Macula Vessel Density and Foveal Avascular Zone Parameters in Exfoliation Glaucoma Compared to Primary Open-Angle Glaucoma

Abstract: Purpose The purpose of this study was to explore macula vessel density and foveal avascular zone (FAZ) parameters in exfoliation glaucoma (XFG) compared to primary open-angle glaucoma (POAG) using optical coherence tomography angiography (OCTA). Methods This was a cross-sectional observational study. Twenty-six XFG and 28 POAG patients with comparable visual field defects on Humphrey 24-2 and 10-2 perimetries were recruited. OCTA scans (3 × 3 mm) centered on the fovea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 68 publications
(91 reference statements)
2
24
0
2
Order By: Relevance
“…Physiological evidence also supports that the macula is more sensitive to hypoxia and ischaemia because it consumes more oxygen than other tissues in the body 17 . Subsequently, macular VD and foveal avascular zone (FAZ) metrics were regarded as potential biomarkers in the clinical evaluation of early glaucoma in recent studies 18 20 . However, few researches have examined macular vasculature in PACG.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological evidence also supports that the macula is more sensitive to hypoxia and ischaemia because it consumes more oxygen than other tissues in the body 17 . Subsequently, macular VD and foveal avascular zone (FAZ) metrics were regarded as potential biomarkers in the clinical evaluation of early glaucoma in recent studies 18 20 . However, few researches have examined macular vasculature in PACG.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The mechanism of glaucomatous optic neuropathy in eyes with PEX-related glaucoma is due to mechanical damage by elevated intraocular pressure, which results in death of retinal ganglion cells 23 with primary open-angle glaucoma, which constitutes evidence for vasculopathy in eyes with PEX. 25 Conversely, there is no evidence to support reduction of optic nerve head blood flow in eyes with TEX.…”
Section: Discussionmentioning
confidence: 99%
“…This vasculopathy may produce synergistic effect on the natural course of PEX-related glaucoma, which may result in greater intraocular pressure fluctuation, more severe clinical manifestations, and greater recalcitrance, compared with primary open-angle glaucoma. Shawn et al found lower macula vessel density in eyes with pseudoexfoliation glaucoma than in eyes with primary open-angle glaucoma, which constitutes evidence for vasculopathy in eyes with PEX [ 25 ]. Conversely, there is no evidence to support reduction of optic nerve head blood flow in eyes with TEX.…”
Section: Discussionmentioning
confidence: 99%